2021
DOI: 10.3389/fcell.2021.778020
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Stem Cells and CART as a Potential Polytherapy for Small Cell Lung Cancer

Abstract: Despite the increasing urgency of the problem of treating small cell lung cancer (SCLC), information on the causes of its development is fragmentary. There is no complete understanding of the features of antitumor immunity and the role of the microenvironment in the development of SCLC resistance. This impedes the development of new methods for the diagnosis and treatment of SCLC. Lung cancer and chronic obstructive pulmonary disease (COPD) have common pathogenetic factors. COPD is a risk factor for lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 170 publications
0
5
0
Order By: Relevance
“…Actively proliferating tumor cells are generally targets for drugs. Meanwhile, progression, metastasis, and recurrence of lung cancer, as well as resistance to therapy, are related to CSCs [ 15 , 28 ]. CSCs with a long resting state (G0 arrest) and high activity of the efflux transport system are insensitive to anticancer drugs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actively proliferating tumor cells are generally targets for drugs. Meanwhile, progression, metastasis, and recurrence of lung cancer, as well as resistance to therapy, are related to CSCs [ 15 , 28 ]. CSCs with a long resting state (G0 arrest) and high activity of the efflux transport system are insensitive to anticancer drugs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, T-lymphocyte therapy should be focused on elimination of CSCs, as well as tumor cells. Thus, CSCs are potential therapeutic targets and diagnostic and prognostic markers for lung cancer [ 15 ]. This approach may be more effective in the early stage of tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we evaluated different populations of CSCs in the lungs. CSCs were identified using common markers such as CD117, CD44, EGF, and Axl, as well as the cell proliferation marker Sox2 [ 27 ]. Interestingly, we have found similar markers in the same combination when mrT-cells were used for cell therapy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…), which have demonstrated great efficacy as a gene-expression-regulating vector in tumor therapy ( 177 ). Hong et al.demonstrated that CAR-T cell-derived exosomes inhibit solid tumors, including triple negative breast cancer and lung cancer, and can affect the tumor microenvironment with relative safety ( 178 , 179 ). Meanwhile, Haque et al.…”
Section: Immune Cell-derived Engineered Exosomes and Tumor Therapymentioning
confidence: 99%